2014
DOI: 10.1111/jnc.12748
|View full text |Cite
|
Sign up to set email alerts
|

S100β as an early biomarker of excitotoxic damage in spinal cord organotypic cultures

Abstract: S100b is a cytoplasmic calcium-binding protein mainly expressed by glia and considered to be a useful biomarker for brain or spinal cord injury. Indeed, clinical studies suggest that the S100b concentration in serum or cerebrospinal fluid may predict lesion outcome and prognosis. The relation of S100b levels to damage severity and its timecourse remains, however, unclear. This study used a validated in vitro model of spinal cord injury induced by kainate-mediated excitotoxicity to investigate these issues. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…This crosstalk potentially affects multiple downstream synaptic processes but also patho-physiological events such as excitotoxicity. Intriguingly, S100B concentrations have been reported high under conditions facilitating excitotoxicity (Mazzone and Nistri, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This crosstalk potentially affects multiple downstream synaptic processes but also patho-physiological events such as excitotoxicity. Intriguingly, S100B concentrations have been reported high under conditions facilitating excitotoxicity (Mazzone and Nistri, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, neural S100 proteins are increased during processes activating NF-κB, such as inflammatory processes (Donato et al, 2013 ) and other insults to the brain. In particular, release of S100B was reported in response to excitotoxicity (Mazzone and Nistri, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, overexpression of GFAP in the brain of animals with experimentally induced diabetes was demonstrated in various brain areas (Nedzvetsky et al, 2012). Various types of brain injury provoke release of S100 family proteins into cerebrospinal fluid and blood (Rothermundt et al, 2003;Michetti et al, 2012), which allows this glial marker to be used as a diagnostic tool to determine CNS damage (Gerlach et al, 2006;Ellis et al, 2007;Mazzone & Nistri, 2014). Several in vitro results have demonstrated that S100β efflux, which was stimulated with oxygen-glucose deprivation and metabolic stress, is independent of the synthesis S100β protein de novo (Davey et al, 2001;Gerlach et al, 2006;Ellis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, they proposed a hypothesis whereby TASK channel inhibition via persistent autocrine activation of the NO/cGMP/PKG cascade could sensitize NOS-expressing neurons to excitotoxic damage in brain neurodegenerative processes via a sustained increase in their excitability. Moreover, Mazzone and Nistri [39] used a validated in vitro model of spinal cord injury induced by kainate-mediated excitotoxicity to explore relation of S100B levels and damage severity and found that S100B represents a useful biomarker of lesion progression as its level is related to the occurrence and severity of neuronal loss due to excitotoxicity. Therefore, MV might cause neuronal damage directly in the brain or cause apoptosis by reducing the protective factor-TASK-1 channel expression.…”
Section: Discussionmentioning
confidence: 99%